DOES HIPPOCAMPAL DAMAGE EXPLAIN MEMORY LOSS IN VASCULAR COGNITIVE IMPAIRMENT?. Issue 11 (14th October 2015) - Hosseini, Akram; Meng, Dewen; Simpson, Richard; Auer, Dorothee
Abstract : Introduction: Cognitive impairment (CoI) is common in old age and following cerebrovascular disease. The contribution of acute and chronic cerebral infarcts and hippocampal integrity to various domains of CoI remains unclear. Methods: 100 patients with recent cerebrovascular ischaemic events and >30% carotid artery stenosis (age: 75.4±9.2, 40% female) received brain MRI. Addenbrooke's cognitive examination was used for assessment. Acute and chronic ischaemic volume was identified on diffusion tensor and FLAIR images. Total ischaemic lesion load (TILL), and mean diffusivity (MD) of bi-hippocampi were calculated. A statistical cognitive prediction model was build using age and vascular risk factors between cognitively impaired subgroup against the normal cognition. Next, TILL and then hippocampal MD were added to the relevant risk factors. AUC for each model was compared. Results: 51% were cognitively impaired, particularly the eldest (P=0.002). Age and TILL were independently associated with CoI (P=0.03), specifically executive dysfunction. Hippocampal MD was significant predictor of overall cognition, particularly memory, after adjusting for age and infarction volume (P=0.001). AUC of model prediction confirmed superior predictability of hippocampal MD for cognition. Conclusion: In vascular cognitive impairment, hippocampal integrity independently contributes to anterograde, long recall and recognition memory, whilst volume of brain infarcts correlates with executive dysfunction.